PERBANKAN SYARIAH DAN PENGANGGURAN: SUATU APLIKASI EMPIRIS TEORI SEARCH AND MATCHING MODEL - Sari Lestari Zaenal Ridho (University of Merdeka Malang, 2013)
The development of shariah banking gave some positive impacts in many fields, including in reducing unemployment,since the growing number of Islamic banks could raise the number of labor employ. Unfortunatelythe equilibrium condition of labor demand and supply was not only necessary through market mechanism, butalso through the job search process, and compatibility with the existing work. Therefore, by using appliedresearch method, this study aimed to describe the opportunities and challenges of shariah banking in reducingthe unemployment rate as empirical application from one of theory unemployment, namely the Search andMatching Model theory.